MEMASTIKAN KEBERLANJUTAN KEGIATAN MENABUNG DI RA TAUFIQURRAHMAN BEJI TIMUR DEPOK - Kartika Nuringsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
In line with the let's save the program in the previous activity, the agenda for this activity aims to ensure the sustainability of saving for children in Raudhatul Athfal Taufiqurrahman Beji Timur Depok. Through collaboration with Bank BRI Agroniaga, abdimas activities have succeeded in opening TabunganKu, so the next task is to help ensure the sustainability of this saving behavior. Thus the approach is carried out in two ways, namely: first by ensuring that the pick-up service facility from Bank BRI Agroniaga officers can run smoothly, while the second way is by motivating through stories themed about saving. The output target is an increase in the amount of savings and a simple story about saving that is appropriate for children's level is composed. The approach is carried out through joint assistance with Bank BRI Agroniaga with evaluation results showing that there are still many savings books whose balances have not increased. Meanwhile, for students who have made additional savings, the value varies between Rp. 300,000, - to Rp. 400,000, -. This happens because learning activities have not been fully face-to-face so that the savings deposit pick-up service process has also not been running. To overcome this condition, some parents took the initiative to add savings independently through transfer to TabunganKu. Concerning the second outcome target, a simple story or fairy tale about saving has been produced. Mrs. Ina as the accompanying teacher has provided education through the fairy tale to touch the hearts of children about the benefits of saving. In line with the activities with children and accompanying teachers, it shows an increase in the number of savings, but this addition has not occurred in all savings. Therefore, the role of parents and teachers is needed to continuously motivate children to save in order to form sustainable saving behavior.